Overview of Nurses' Knowledge Regarding the Implementation of Basic Life Assistance in the Emergency Installation of the Pelamonia Hospital Makassar - Hermansyah , Hermansyah (Journal of Asian-african Focus in Health, 2023)
Emergency nursing nursing is a comprehensive nursing service provided to patients with acute injuries or life-threatening illnesses. Based on data obtained from RSU Sayang Rakyat Makassar , the number of patients requiring basic life support in 2013 was 60 patients, in 2014 there were 80 patients, and in 2015 there were 119 patients. Objective study is For get the picture knowledge nurse about implementation help life Basics in Installation Bad Emergency RSU Sayang Rakyat Makassar. Type study This is Observational research is descriptive . Population in study This are all nurses on duty at the installation Bad The emergency situation at the Sayang Rakyat Hospital in Makassar was 19 people . Sample amount 19 people use technique total sampling . Research was carried out starting date 13 to 18 April 2016. Data collected with using a questionnaire . The research results show that Most of the respondents had good knowledge about implementing basic life support, namely 18 people ( 94, 7 %), and the majority of nurses carried out basic life support according to 2010 AHA provisions, namely 17 people (89.5%). Based on results study concluded that Most nurses have good knowledge about implementing basic life support, and most nurses carry out basic life support in accordance with the provisions of AHA 2010. It is recommended that hospital institutions need to increase the knowledge and skills of nurses regarding basic life support by holding seminars or continuous training. so that nurses are able to provide services to patients experiencing emergency conditions, as well as evaluating and monitoring nurses who have not and have undergone training.